Community Structure of Mollusca in Sulamanda Beach, Kupang Regency, East Nusa Tenggara - Kana, Ferderika Rame; toruan, lumban nauli lumban; Saraswati, Suprabadevi Ayumayasari (Jurnal Moluska Indonesia, 2024)
Molluscs (Gastropods and Bivalves) are organisms that are sensitive to environmental changes. This research was conducted at Sulamanda Beach, Mata Air Village, Central Kupang Subdistrict, Kupang Regency. This study aims to determine the community structure of Gastropods and Bivalves using the approach of species density, diversity, uniformity and dominance. Information on the community structure of Gastropods and Bivalves in Sulamanda Beach is needed in an effort to support sustainable tourism management. This research used observation method. Determination of stations using purposive sampling method. Gastropod and Bivalve sampling used line transect method by installing a 1 X 1 m² quadrant frame. Sampling of water samples for water parameters was carried out at each observation station. The results showed that Sulamanda Beach has 16 species of mollusks consisting of 12 species of gastropods from 5 families and 4 species of bivalves from 2 families. The species with the highest density was Murichorda fiscellum with a value of 2.4 Ind/m². The diversity index of Gastropods and Bivalves tends to be high with a uniformity index value tending to be moderate, while the dominance index shows a value that tends to be low. The physical and chemical parameters of the waters show that the water conditions are in good condition because they are still within the tolerance limits of the two classes. The bottom substrate is dominated by rocky sand. Therefore, the overall community structure of Gastropods and Bivalves in Sulamanda Beach, Kupang Regency is considered stable and balanced.